Spatial Fingerprinting of Biogenic and Anthropogenic Volatile Organic Compounds in an Arid Unsaturated Zone - Green, C.T. (2020)
This study synthesized 17 yr of VOC data from the Amargosa Desert Research Site in Nevada with the goal of improving understanding of spatial and temporal variations that distinguish sources of VOCs from a landfill and from ambient sources including biogenic VOCs (bVOCs). Gas samples were collected from 1999 to 2016 from an array of shallow sample points (0.5‐ and 1.5‐m depth) and from vertical profiles at three deep boreholes: two (109 m deep) near the border of a waste facility (33 and 100 m distant), and one (29 m deep) in a remote area 3 km to the south. Samples were analyzed for target VOCs and a subset was analyzed for non‐target VOCs to enumerate a greater variety of potential bVOCs. Principal components analysis of the target and non‐target VOCs provided an assessment of the spatial variability of VOCs originating from the landfill site and from ambient sources. Ambient VOCs occurred at all sample sites across a range of depths, and most were consistent with biogenic origins, indicating for the first time the presence of bVOCs in the deep unsaturated zone. Because some VOCs have both anthropogenic and biogenic sources, discrimination of sources can be important for estimating the extent and migration of anthropogenic plumes in arid unsaturated zones.